2003
DOI: 10.1038/nature01731
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal populations and single cells representing learned auditory objects

Abstract: The neural representations associated with learned auditory behaviours, such as recognizing individuals based on their vocalizations, are not well described. Higher vertebrates learn to recognize complex conspecific vocalizations that comprise sequences of easily identified, naturally occurring auditory objects, which should facilitate the analysis of higher auditory pathways. Here we describe the first example of neurons selective for learned conspecific vocalizations in adult animals--in starlings that have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
199
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 234 publications
(208 citation statements)
references
References 24 publications
7
199
2
Order By: Relevance
“…Learned visual associations in monkeys are reflected by association-selective representations in higher visual areas of the temporal cortex (21,22), with top-down activation by the PFC contributing to prospective representations of the choice picture to be recalled (19). Changes to stimulus-selective representations in higher sensory areas have also been reported in anesthetized starlings trained on auditory discriminations (23)(24)(25). Single neurons as well as population activity in auditory association areas contained information about the behavioral relevance of different sounds.…”
Section: Discussionmentioning
confidence: 90%
“…Learned visual associations in monkeys are reflected by association-selective representations in higher visual areas of the temporal cortex (21,22), with top-down activation by the PFC contributing to prospective representations of the choice picture to be recalled (19). Changes to stimulus-selective representations in higher sensory areas have also been reported in anesthetized starlings trained on auditory discriminations (23)(24)(25). Single neurons as well as population activity in auditory association areas contained information about the behavioral relevance of different sounds.…”
Section: Discussionmentioning
confidence: 90%
“…Measurement of long-term response habituation in NCM, by both electrophysiology and the study of the song stimulation-induced up-regulation of ZENK, has suggested that this area might encode the long-lasting sensory memory of the TUT (31,40). Other experiments point to the fact that NCM and CM might be involved in short-term plasticity related to song discrimination (18,19,48). The greater representation of TUT and BOS revealed by fMRI in our experiments therefore might reflect an important aspect of the sensory memory for these developmentally salient familiar stimuli.…”
Section: Familiar Song Stimuli Show Selective Differential Topographymentioning
confidence: 99%
“…In parallel with song motor learning, auditory song selectivity gradually emerges during development (13)(14)(15)(16)(17). Robust sensory responses to auditory stimuli have been recorded in the primary auditory area in the caudal telencephalic region (field L), the caudomedial nidopallium (NCM), the caudal mesopallium (CM), and the caudomedial ventral hyperstriatum (18)(19)(20)(21), as well as in the song nuclei HVC, LMAN, X, and nucleus interface of the nidopallium (22)(23)(24)(25)(26)(27)(28). Sensory representation of birdsong in the song nuclei and the secondary auditory areas NCM and CM is characterized by response selectivity to song ownership, familiarity, and species-specific features.…”
mentioning
confidence: 99%
“…Nevertheless, female zebra finches can learn to recognize songs to which they have been exposed, and they develop a preference for these songs (Riebel, 2000;Riebel et al, 2002). Several studies have shown that both the NCM and the CMHV are involved in processing conspecific songs in female songbirds (Chew et al, 1996;MacDougall-Shackleton et al, 1998;Duffy et al, 1999;Gentner et al, 2001;Bailey et al, 2002;Sockman et al, 2002;Bailey and Wade, 2003;Gentner and Margoliash, 2003;Grace et al, 2003;Maney et al, 2003;Phillmore et al, 2003), as well as in female budgerigars . Preliminary results from our own laboratory indicate that, in female zebra finches, the CMHV may be part of the neural representation of learned tutor song (Terpstra et al, 2001).…”
Section: The Role Of the Cmhv In Tutor Song Representationmentioning
confidence: 99%